(untitled) (Majalah Kedokteran Bandung, 2020)
Cystatin C is a 13 kD molecular-weight protein synthesized by all nucleated cells which functions as a cysteine protease inhibitor. Cystatin C is detectable when kidney function decreases due to the excessive accumulation of nephrotoxic substances such as copper. Previous studies have proven that white turmeric rhizome can act as a nephroprotector agent at a dose of 500mg/BW. The purpose of this study was to compare Cystatin-C marker and serum creatinine as biomarkers in the examination of acute kidney injuries induced by nephrotoxic substance. This was a post-test only controlled experimental study on wistar strain male rats that were divided randomly using simple random sampling approach into three groups: normal control group, treatment control group (Curcumin for 2 weeks followed by CuSO4 for 3 days at each weekend), and CuSO4 pentahydrate control group. This study was conducted in Faculty of Pharmacy and Faculty of Medicine of the University of North Sumatera in May to August 2019. Results were normally distributed with significant differences in levels of Cystatin-C, creatinine, and protein serum due to differences in the treatment of each group (p<0.05). Serum Cystatin-C is proven to be a more sensitive biomarker for detecting acute kidney damage compared to serum creatinine. Peran Cystatin-C sebagai Biomarker Serum dalam Memprediksi Fungsi Glomerulus-Terkait dengan Cedera Ginjal Akut yang Dipicu Tembaga Cystatin C adalah protein dengan berat molekul 13 kD disintesis oleh setiap sel yang memiliki inti berfungsi sebagai inhibitor protease sistein. Cystatin C terdeteksi ketika fungsi ginjal menurun oleh zat nefrotoksik seperti tembaga. Tembaga merupakan salah satu logam yang dapat menjadi zat nefrotoksik bila terakumulasi berlebihan. Ekstrak rimpang kunyit putih memiliki manfaat sebagai nefroprotektor dengan dosis mg/kgBB. Penelitian ini dilakukan untuk mengetahui perbandingan Cystatin-C dan kreatinin serum sebagai biomarker dalam pemeriksaan kerusakan ginjal akut akibat zat nefrotoksik. Penelitian eksperimental ini menggunakan the post test only control group design dengan teknik simple random sampling. Penelitian ini dilakukan di Fakultas Farmasi dan Fakultas Kedokteran Universitas Sumatera Utara pada bulan Mei hingga Agustus 2019. Tikus jantan dengan galur wistar dibagi tiga kelompok; kontrol normal, kontrol kunyit putih (500 mg/kgBB) sebagai pre-treatment (curcumin selama 2 minggu diikuti CuSO4selama 3 hari di setiap akhir pekan), dan kontrol CuSO4 pentahidrat. Hasil analisis data terdistribusi normal dan terdapat perbedaan yang signifikan kadar Cystatin-C, kreatinin dan protein serum pada setiap kelompok dimana nilai p<0.05. Cystatin-C serum sebagai biomarker lebih sensitif dalam mendeteksi kerusakan ginjal akut dibanding dengan kreatinin serum.